(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The study investigates the role of investigative forensic accounting techniques in limiting financial and administrative corruption. It focuses on the control measures that forensic accountants can apply to detect and reduce fraudulent practices. The empirical results confirm the relevance of these techniques in complex financial environments. The study recommends strengthening their application as a key anti-fraud tool.